Outcome of patients activating an unrelated donor search for severe acquired aplastic anemia. Issue 10 (1st August 2013) - Maury, Sébastien; Balère‐Appert, Marie‐Lorraine; Pollichieni, Simona; Oneto, Rosi; Yakoub‐Agha, Ibrahim; Locatelli, Franco; Dalle, Jean‐Hugues; Lanino, Edoardo; Fischer, Alain; Pession, Andrea; Huynh, Anne; Barberi, Walter; et al.
<x xml:space="preserve">Abstract</x> Patients with severe aplastic anemia (SAA) without a sibling donor receive immunosuppressive treatment (IST) with anti‐thymocyte globulin (ATG). In the case of no response to IST, a voluntary unrelated donor (VUD) search is usually started. This study analyzes the outcome of ATG‐refractory SAA patients activating a VUD search. Of 179 patients, 68 had at least one HLA‐A, –B, and –DR matched donor identified and underwent HSCT while 50 also with a donor were not transplanted because of early death (8), late response to IST (34), transplant refusal (1), or other (7). Conversely, 61 had no matched donor, 13 of those ultimately received a mismatched HSCT. All but one received marrow stem cells. Among patients aged <17 years, those with at least one matched donor had a significant higher 4‐year survival as compared to others (79% ± 6% versus 53% ± 10%, P = 0.01). There was also a survival advantage independent of recipient age when the donor search was initiated in the recent 2000–2005 study‐period (74% ± 6% versus 47% ± 10%, P < 0.05). In multivariate analysis, the identification of a matched VUD tended to impact favourably on survival in patients with a recent donor search (P = 0.07). This study provides evidence for the use of unrelated donor HSCT in children and adults with IST‐refractory SAA. Am. J. Hematol. 88:868–873, 2013. © 2013 Wiley Periodicals, Inc.